The Testing for Information Gathering Using OWASP Testing Guide v4 (Case Study : Udayana University SIMAK-NG Application) - Daniswara, Rasendriya Revo; Sasmita, Gusti Made Arya; Pratama, I Putu Agus Eka (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2020)
Web Application is the most used platform to develope an information system. The increased of web application technology is comparible as the risk, therefore web application must be tested first to make sure there is no risk or security issues on that application before it’s launch to public. Penetration testing is a method that test the web application security risk. The first step to do penetration testing is testing for information gathering, it is used help the tester to known the specification and vulnerability of the application. This study will implement testing for information gathering to Udayana University SIMAK-NG (Academic Information System) Application  using OWASP Testing Guide Version 4 framework to known there is  any security issues on that application. there are ten things that were tested, that is from OTG-INFO-001 until OTG-INFO-010 and the result is seven test get positif value.